(untitled) (Proceedings OPTIMAL, 2025)
The tendency to neglect oral health is usually based on a lack of knowledge. to increase knowledge, a health promotion process supported by a media is needed. lesflets have the advantage of being able to meke it easier for users to remember things that have been taught or communicated can adjust and learn independently and practically because it reduce the need for note taking while posters faciliated understanding, and icrease enthusiasm for learning. the porpose of this study was to determine the difference in dental and oral hygiene knowledge between counseling and leaflet and poster media in grade VIOI MTSN 8 Agam students, ampek Angkek District, Agam Regency. The type of research used is quasi-experimental with pretyest and postest designs . The population of this study was all grade VII students of MTSN 8 Agam, asmpek Angkek District Agam Regency . Totaling 115 students. The sampel inthis study was 90 people, the samplingtechnique used was simple random sampling. How to collect data by filling out pretest-posttest questionnaires on dental and oral hygiene, counseling media leaflets and posters. data analysis was used, namely univariate and bivariate analysis. The results showed that students knowledge bbefore beinggien counseling on dental and oral hygiene obtained 26,7% results with good criteria and after beinggiven counseling with leaflet media increased to93,3%. The knowlwdge of student beforebeing given dental and oral hygiene counseling obtained results of 28,9 with goodcriteria and after being given counseling with poster media increased to95,6%. The conclusion in this study is that leaflet media and oral hygiene Itis recomended to respondents to increase their knowledgeabout dental and aoral hygiene by reading through the mass media that exists today and applying it in their daily lives.